NON FUNGIBLE TOKEN SEBAGAI ASET DIGITAL DALAM PANDANGAN FIQH MUAMALAH - Robbani, Shofa; Khoiria Ningrum, Ifa (Universitas Nahdlatul Ulama Sunan Giri, 2022)
The phenomenon of buying and selling online continues to grow, especially in 2022, when Ghozali shocked the Indonesian people by selling 933 non-fungible token digital works for 1.5 billion on the OpenSea Online Market. But not all people respond, because everyone can sell other people's art, sell images that contain pornography, and commit fraud under the guise of investment. In Sharia economic law, on the other hand, the element of fraud and the sale of something that does not belong to him are prohibited. The mechanism of buying and selling non-fungible tokens on the OpenSea online market is discussed in this study, as well as how the law is based on Islamic economics.This type of research uses a qualitative approach by seeking direct data from parties involved in buying and selling non-fungible tokens on the Opensea online marketplaces, from journals, articles, books, and other sources. The theory of